Beginner's guide to digital painting in Photoshop sci-fi & fantasy - Moss, Annie (Worcester, United Kingdom 3dtotal Publishing, 2016)
"Beginner's guide to digital painting in Photoshop: sci-fi and fantasy is an ideal guide for artists wanting to create imaginative and compelling genre art. Established artists share their industry experience by covering such aspects as how to design an interesting composition, achieving correct perspective, and conveying moods with color and light. Insightful step-by-step tutorials, and a handy quick tips section that covers how to paint elements that are integral to sci-fi and fantasy art, make this an invaluable resource for those looking to learn new skills, as well as those pursuing the next level." -- Provided by publisher
Includes index.
Keywords: Adobe Photoshop; Painting -- Digital techniques